(untitled) (Papeles, 2023)
This article emerges from some reflections made as of the developed inquiries by the authors about the Social Work´s origins and trajectories in the city of Buenos Aires. The analysis’ focus is centered in the Social Work’s process of institutionalization and professionalization during the 1930s, through the configuration and development of social policies, in relation to the perspective of hygiene, social medicine and eugenics. Along this line, these events were characterized by the predominance of the feminization and maternalism processes, delimiting women in certain socio-occupational spaces, positions, and professional tasks through the sexual division of labor.